Knock me up, knock me down : images of pregnancy in Hollywood films - Oliver, Kelly, 1958- (Columbia University Press, 2012)
The image of a heavily pregnant woman, once considered ugly and indecent, is now common to Hollywood film. Kelly Oliver investigates this curious shift and its reflection of changing attitudes toward women's roles in reproduction and the family. Reading various films, the book investigates pregnancy as a vehicle for romance, a political issue of choice, a representation of the hosting of others, a prism for fears of miscegenation, and a screen for modern technological anxieties.